THE GROWTH PERFORMANCE OF WHITE SNAPPER (Lates calcarifer) FINGERLINGS IN ODE AQUACULTURE AND AGRICULTURE HATCHERY UNIT, BRUNEI-MUARA BRUNEI DARUSSALAM DISTRICT - Ritonga, Lusiana BR; Harijono, Teguh; Asmarany, Anja; Widodo, Agus; Aonullah, Asep Akmal; Akbar, M.Baihaqi; Affisramyraj, Rizky (Aurelia Journal, 2025)
White snapper (Lates calcarifer) is a high value aquaculture commodity with increasing market demand. This study aimed to analyzed the growth performance of white snapper fry during the nursery phase at the ODE Aquaculture and Agriculture Hatchery Unit, Brunei-Muara District, Brunei Darussalam, from March to June 2023.The nursery utilized controlled fiberglass tanks equipped with aeration and a flow-through water system. Two types of tanks were used: rectangular tanks measuring 4 × 1.5 × 1 m (capacity: 6,000 L) and circular tanks with a diameter of 2 m (capacity: 3,140 L). A total of 100,000 fry were stocked, with 30,000–40,000 fry per tank. Observed parameters included survival rate (SR), absolute length growth rate, absolute weight growth rate, specific growth rate (SGR), and feed conversion ratio (FCR). Water quality parameters measured were temperature, salinity, and pH. Results indicated an absolute length growth rate of 1.2 cm/week, surpassing previous studies reporting only 0.4 cm/week. The absolute weight growth rate was 1.3 g/week, exceeding the 0.6–1 g/week range reported in other research. The FCR was 0.33, demonstrating excellent feed efficiency. However, the survival rate was 30.77%, below the standard for controlled nursery systems (>50%), likely due to high stocking density and cannibalism. Harvest size ranged from 8 to 9 cm. Water quality remained stable, with temperatures between 31–32.5°C, pH levels from 7.6–8.3, and salinity ranging from 30–32 ppt. Despite the low survival rate attributed to high stocking density, the nursery phase at this facility achieved commendable growth rates compared to previous studies. This success is supported by stable water quality and the provision of high-protein feed.